Comprehensive Physiology 2014
DOI: 10.1002/cphy.c140005
|View full text |Cite
|
Sign up to set email alerts
|

Neural Control of the Circulation: How Sex and Age Differences Interact in Humans

Abstract: The autonomic nervous system is a key regulator of cardiovascular system. In this review we focus on how sex and aging influence autonomic regulation of blood pressure in humans in an effort to understand general issues related to how the autonomic nervous system regulates blood pressure, and the cardiovascular system as a whole. Younger women generally have lower blood pressure and sympathetic activity than younger men. However, both sexes show marked inter-individual variability across age groups with signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 111 publications
2
98
1
3
Order By: Relevance
“…26 In the present study, blood flow at rest was found to be lower in the postmenopausal women than in the premenopausal women, which is in agreement with a higher basal sympathetic tone in the postmenopausal group. The central sympathoinhibitory effect of estrogen is likely to be amplified by enhanced β 2 -mediated vasodilation as β 2 -adrenergic blockade augments the vasoconstrictor response to norepinephrine in premenopausal women to a level similar to that of postmenopausal women.…”
Section: Hypertensionsupporting
confidence: 89%
“…26 In the present study, blood flow at rest was found to be lower in the postmenopausal women than in the premenopausal women, which is in agreement with a higher basal sympathetic tone in the postmenopausal group. The central sympathoinhibitory effect of estrogen is likely to be amplified by enhanced β 2 -mediated vasodilation as β 2 -adrenergic blockade augments the vasoconstrictor response to norepinephrine in premenopausal women to a level similar to that of postmenopausal women.…”
Section: Hypertensionsupporting
confidence: 89%
“…Given the involvement of MSNA in blood pressure regulation, reductions in MSNA in individuals with MS, taken together with the current findings, indicate an impaired sympathetic modulation of the vasculature in MS in response to hypotensive stimuli. Given that women are two to three times more likely to be diagnosed with MS along with strong evidence that suggest vasoconstrictor responsiveness is blunted in young women, the impact of reduced baroreflex-mediated vasoconstriction may be compounded (Hogarth et al 2007;Joyner et al 2015;Kneale et al 2000;National Multiple Sclerosis Society 2016b). Furthermore, men living with MS progress more rapidly, which may lead to greater carotid baroreflex dysfunction (20).…”
Section: Discussionmentioning
confidence: 99%
“…This proposal requires further investigation and the situation may be different in healthy subjects and those with elevated sympathetic drive a priori (Roveda et al 2003;Carter and Ray 2015). It is also now clear that important differences in autonomic function may result from differences in receptor density and function that exist between men and women of different ages (Green et al 2015;Joyner et al 2015).…”
Section: Some Things We Do Not Know About Exercise Training and Artermentioning
confidence: 99%